Two new damselfly species from Polillo Island, Philippines (Odonata: Platystictidae) - Villanueva, Reagan Joseph T.; Schorr, Martin (Zootaxa, 2011)
Drepanosticta wildermuthi spec. nov. and Sulcosticta vantoli spec. nov. are described and illustrated. The two species are compared with their nearest relatives, D. moorei van Tol & Müller and S. viticula van Tol, respectively. Drepanosticta wildermuthi spec. nov has shorter anterior lobe processes compared to D. moorei. Sulcosticta vantoli spec. nov. has a simpler paraproct structure compared to S. viticula.